A universalidade poética de Rilke na formação do Grupo dos Novos: tradução e confluências na Amazônia brasileira - VANSILER, João Jairo Moraes (Universidade Federal do Pará, 2014)
The purpose of this Master's thesis is to identify how translations of Rilke's poetry were relevant in the scenario had been published, on magazine “Suplemento Literário da Folha do Norte” - SL/FN and others. We believe that these translations were indicative of a rise in the process of literary universalization on “Pará”, to innovations of Modern Art Week, 1922. These translations were crucial to the literary formation of “Grupo dos Novos”, which was composed by Benedito Nunes, Mário Faustino, Plinio Paulo Abreu and others in addition to the German anthropologist Peter Paul Hilbert. For this work we explore the concepts of Weltliteratur by Goethe and Reflexionsmedium by Benjamin. We also use the concept of Bildung, from the reading of Antoine Berman, which relates it to the translation. These concepts will link to history, philosophy of language and translation in order to reflect the impact of these translations in the Brazilian Amazon, at the time they were made. Through the translation theory of Haroldo de Campos, we aim to investigate possible confluences in poetic productions and criticism by Mario Faustino, Manuel Bandeira and Paulo Plínio Abreu as a result of the relationship between the work of these poets and Rilke, promoted through these translations.